National Unity Questions and the IPOB Movement in South-East Nigeria: A Critical Appraisal - Oluka, Lucas (Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
ABSTRACTThis study examined the underlying causes of the separatist movement led by the Indigenous People of Biafra (IPOB), which calls into question the unity of Nigeria and calls for its secession. According to the investigation, the military coup d'état in 1966 and the counter coup that occurred seven months later, which was followed by the genocide against people of Igbo ancestry were the main causes of the unrest. Additionally, it is said to have contributed to alleged marginalisation of the Igbos in the Federal Republic of Nigeria's (FRN) administration. In this study, descriptive analysis was employed. The study used secondary sources of data, especially those from books, journal articles, daily and periodicals, and the internet. The Choice theory, also known as the plebiscitary theory of secession by Allen Buchanan (2004) served as the basis for the study's framework. The investigation suggests that the 1999 Federal Republic of Nigeria (FRN) Constitution, as amended, be reviewed in order to address the grave national concerns brought up by the IPOB's call for secession. Overall, the paper recommended that immediate and necessary steps should be taken by the Executive arm of Government and the National Assembly to restructure the country’s self-styled federal system of administration which may put an end to this form of agitation, not only of the IPOB secessionist scheme, but also of such designs of other aggrieved ethnic nationalities in the country.